2015
DOI: 10.5935/1678-9741.20150045
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraoperative diltiazem infusion on flow changes in arterial and venous grafts in coronary artery bypass graft surgery

Abstract: ObjectiveThis study aimed to show the effects of intra-operative diltiazem infusion on flow in arterial and venous grafts in coronary artery bypass graft surgery.MethodsHundred fourty patients with a total of 361 grafts [205 (57%) arterial and 156 (43%) venous] underwent isolated coronary surgery. All the grafts were measured by intraoperative transit time flow meter intra-operatively. Group A (n=70) consisted of patients who received diltiazem infusion (dose of 2.5 microgram/kg/min), and Group B (n=70) didn't… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Four trials reported arterial graft flow measurements, but the data were insufficient for synthesis. One study revealed that, compared to placebo, continuous perioperative IV infusion of DILT significantly increased IMA blood flow[ 41 ]. Results from two other studies showed that patients receiving NTG had significantly higher blood flow in IMA or radial grafts[ 50 , 51 ], while a study comparing DILT to NTG showed that patients in the DILT group had significantly higher IMA blood flow[ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four trials reported arterial graft flow measurements, but the data were insufficient for synthesis. One study revealed that, compared to placebo, continuous perioperative IV infusion of DILT significantly increased IMA blood flow[ 41 ]. Results from two other studies showed that patients receiving NTG had significantly higher blood flow in IMA or radial grafts[ 50 , 51 ], while a study comparing DILT to NTG showed that patients in the DILT group had significantly higher IMA blood flow[ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies in vitro and in vivo have consistently demonstrated that CCBs, topically applied or directly injected into the grafts, can significantly increase blood flow in human IMA and the radial artery (RA) grafts. Data from studies by Erdem[ 41 ] and Tabel[ 34 ] showed that continuous IV infusion of DILT is superior to both placebo and NTG in improving blood flow in dissected left IMA and RA segments before graft anastomosis. Although there were no data of direct flow measurement postoperatively, the lower incidence of cardiac ischemia and cardiac arrhythmia from the current meta-analysis indicated that coronary blood flow was likely better maintained early postoperatively in patients who received perioperative DILT infusion.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no de nitive anatomical evidence supporting that perioperative continuous iv application of diltiazem had a direct vasodilatory effect on coronary grafts after the sternum was closed. Diltiazem became the preferred antispasmodic agent because, compared to nitroglycerine, it had more favorable perioperative outcome pro les, including lower incidences of new onset A-b and cardiac ischemia 7,9,21,22 . Noticeably, data from these RCTs also suggest that patients on diltiazem may need prolonged hemodynamic support from inotropic and/or vasoactive support, indicating that the usage of diltiazem may have potential negative perioperative and long-term outcome impacts 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, numerous drugs have been investigated in RCTs for preventing graft spasm 6 , among which certain calcium channel blockers (CCBs), e.g., diltiazem and nitroglycerin, were the top choices because of their well-known coronary selectivity and their proven track records of reliable symptomatic relief of unstable angina. Data from these RCTs, mostly conducted between the 1980s and early 2000s with small sample sizes on LITA grafts, suggested that, by direct ow check intraoperatively, both diltiazem and nitroglycerin increased arterial graft blood ow when applied locally and/or systemically, while when applied through continuous intravenous (iv) infusion perioperatively, diltiazem was superior to nitroglycerin for lower incidences of perioperative cardiac ischemia and arrythmia [7][8][9][10][11][12][13][14][15] . Currently, perioperative continuous iv infusion of diltiazem is frequently chosen as the intervention for preventing arterial graft spasms, especially for patients who receive RA grafts; however, its perioperative and long-term outcome bene ts remain uncon rmed.…”
Section: Introductionmentioning
confidence: 99%
“…It is another commonly applied vasodilator agent to prevent vasospasm and increase flow of coronary artery bypass conduits during CABG. Intraoperative intravenous infusion of diltiazem in addition to topical application of papaverine to test LITA flow was assessed by Erdem O et al [ 27 ] , and the authors found that the maneuver significantly increased the arterial graft flows as well as provided lower incidence of atrial fibrillation during the intraoperative and postoperative periods [ 27 ] . Other than the flow alteration properties of diltiazem, apoptotic properties of this agent on tissues were also assessed in the literature.…”
Section: Discussionmentioning
confidence: 99%